2017
DOI: 10.1248/bpb.b16-00972
|View full text |Cite
|
Sign up to set email alerts
|

Previous Dosage of Allopurinol Is a Strong Determinant of Febuxostat Efficacy

Abstract: Febuxostat has currently played pivotal role in the treatment of hyperuricemia, but there is little comprehensive information for the determinants of individual difference in efficacy of febuxostat. Therefore, the present study, a retrospective investigation, was carried out to analyze the effects of patient characteristics on the efficacy of febuxostat. A total of 225 patients who were continuously prescribed the same dose of febuxostat for 8-12 weeks from the initial therapy were enrolled in the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Consistent with previous studies, baseline serum urate was independently associated with the decrease in serum urate. 24,25 Chino et al 26 also reported that patients with higher baseline serum 7 found that a stepwise dose escalation of febuxostat can be an effective alternative to prophylaxis with low-dose colchicine. Moreover, gout flares may be masked by prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous studies, baseline serum urate was independently associated with the decrease in serum urate. 24,25 Chino et al 26 also reported that patients with higher baseline serum 7 found that a stepwise dose escalation of febuxostat can be an effective alternative to prophylaxis with low-dose colchicine. Moreover, gout flares may be masked by prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, baseline serum urate was independently associated with the decrease in serum urate. 24 , 25 Chino et al 26 also reported that patients with higher baseline serum urate experienced greater reductions in serum urate after taking an SGLT2 inhibitor. In multivariate Poisson regression analyses 2 considering baseline serum urate, it was found that baseline serum urate was independently associated with the number of gout flares, while Δ serum urate 0–12 weeks was no longer a significant risk factor.…”
Section: Discussionmentioning
confidence: 99%